JUSTIFICATION OF CRITICISM OF THE INTERNATIONAL FINANCIAL INSTITUTIONS - Đonlagić, Dženan; Kožarić, Amra (Economic Annals, 2010)
As more than half a century has passed since the establishment of the international financial institutions (IMF, World Bank), this paper analyzes the opinion that these institutions have not accomplished their mission. They generally admit that they have not succeeded in the activities that they set out to accomplish, a propos of gathering funds for countries faced with economic gaps and helping them to maintain long term economic growth and development. We show that these financial institutions have done nothing to reduce poverty and financial disparities, to increase their own transparency, responsibility and management, especially with the public participation of developing countries, or to create a more effective loans system. In this paper the main goal of research is to explore the arguments pro and contra the strategic effect, policy, and working methodology of the international financial institutions in view of finding a solution to the global financial crisis and global prevalent financial problems, and also to consider the reasons for the justification or otherwise of their being part of the global financial system.